2013
DOI: 10.1051/0004-6361/201219867
|View full text |Cite
|
Sign up to set email alerts
|

Properties of ultra-cool dwarfs withGaia

Abstract: Context. The Gaia catalogue will contain observations and physical parameters of a vast number of objects, including ultra-cool dwarf stars, which we define here as stars with a temperature below 2500 K. Aims. We aimed to assess the accuracy of the Gaia T eff and log (g) estimates as derived with current models and observations. Methods. We assessed the validity of several inference techniques for deriving the physical parameters of ultra-cool dwarf stars: Gaussian processes, support vector machines, k-nearest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 43 publications
1
41
0
Order By: Relevance
“…Smart et al (2017) estimated the Gaia magnitude from J magnitude and spectral type of spectroscopically confirmed objects and found that 1010 L and 58 T are brighter than G est = 21.5, and 543 L and 10 T are brighter than G est = 20.3. Sarro et al (2013) predicted similar numbers using a more theoretical approach.…”
Section: Comparison With Modelsmentioning
confidence: 79%
“…Smart et al (2017) estimated the Gaia magnitude from J magnitude and spectral type of spectroscopically confirmed objects and found that 1010 L and 58 T are brighter than G est = 21.5, and 543 L and 10 T are brighter than G est = 20.3. Sarro et al (2013) predicted similar numbers using a more theoretical approach.…”
Section: Comparison With Modelsmentioning
confidence: 79%
“…ESA's Gaia space astrometry mission (Perryman et al 2001;de Bruijne 2012) will perform astrometry of stellar objects brighter than Gaia magnitude G 20 and will therefore deliver data for several hundred UCDs (Smart et al 2008;Sarro et al 2013). The M/L transition objects studied here have an average magnitude of I ∼ 17 and G − I ∼ 1.6, using V − I ∼ 4.5 (Dahn et al 2008) and the colour-colour-relations of Jordi et al (2010), which means that they lie at the faint end of the Gaia magnitude range.…”
Section: Our Project In the Context Of Gaiamentioning
confidence: 99%
“…L and T (hereafter LT) dwarfs are very cool faint objects that are either substellar or at the stellar-substellar boundary (Delfosse et al 1997;Martín et al 1999;Kirkpatrick et al 1999;Burgasser et al 2006a;Dieterich et al 2014). In the billion-object catalogue of Gaia, there will be direct observations of about a thousand LT dwarfs (Sarro et al 2013;Smart 2014). This sample, even though it is relatively small, will be more homogeneous, accurate, complete and Figure 1.…”
Section: Introductionmentioning
confidence: 99%